Acute appendicitis: clinical, surgical and pathological concordance in a Peruvian emergency hospital: Apendicitis aguda: concordancia clínica, quirúrgica y anatomopatológica en un hospital de emergencias peruano - Rafael Parhuana, Merylin R. (2022)
Introduction: Acute appendicitis is the most frequent pathology in surgical emergency. The timeliness and effectiveness of the diagnosis is a parameter for evaluating the quality of care. Objective: To determine the concordance between clinical, surgical and pathological diagnoses in patients with acute appendicitis, “José Casimiro Ulloa” Emergency Hospital, Lima - Peru, 2018. Materials and methods: Observational, cross-sectional, retrospective, analytical study. Medical records of 222 patients diagnosed with acute appendicitis in 2018 were reviewed. Sample calculation with known population (1200), probability sampling. Patients> 18 years of age diagnosed with acute appendicitis, who had undergone surgery, had a pathological study, excluding pregnant women and patients with comorbidities. Data were processed and analyzed with SPSS v.25, descriptive statistics and kappa coefficient were used to analyze agreement, using the Landis and Koch assessment: mild agreement (Kappa = 0.01-0.20), acceptable (0, 21 -0.40), moderate (0.41-0.60), considerable (0.61-0.80) and almost perfect (0.81-1). Results: Adults (50.9%), males (56.8%) predominated. (83.8%) were clinically diagnosed as appendicitis requiring surgery. The predominant surgical diagnosis was a suppurative appendix (32.4%) and a predominant pathological diagnosis of the phlegmonous appendix (72.7%). A case of normal appendix in pathological diagnosis. The clinical-surgical diagnostic agreement was (kappa = 4.18), clinical-pathological diagnosis (kappa = 0.66), and the surgical and pathological diagnostic agreement (kappa = 0.497). Conclusions: A moderate concordance was found between clinical - surgical diagnosis, considerable concordance between clinical - pathological diagnosis, reaffirming the clinical importance in decision-making for a timely surgical intervention. Surgical and pathological diagnostic agreement was moderate, observing a moderate degree of certainty from surgeons and pathologists.